2022
DOI: 10.1021/acschemneuro.2c00418
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-propionic Acid Attenuates HI-Related Blood–Brain Barrier Injury in Neonatal Rats by Modulating the PXR Signaling Pathway

Abstract: The blood−brain barrier (BBB) is an important physiological barrier of the human body contributing to maintaining brain homeostasis and normal function. Hypoxic-ischemic (HI)-related brain injury is one of the main causes of neonatal acute morbidity and chronic disability. The previous research of our group confirmed that there was serious BBB destruction during HI brain injury. However, at present, the protection strategy of BBB is very limited, and further research on the protection mechanism is warranted. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Also kaempferol attenuated LPS-induced BBB dysfunction by counteracting the increase of BBB permeability and the degradation of TJs proteins such as occludin-1 and claudin-1, as well as the gap junction protein connexin 43[58]. Regarding metabolites, indole-3-propionic acid was shown to attenuate hypoxic-ischemic-induced BBB leakage in neonatal rats, holding protective effects on rat BMEC cell viability and proliferation, as well as in AJs and TJs proteins modulation[59]. In male Wistar ischemic rats exposed to dusty particulate matter, it was observed that pretreatment with gallic acid reversed BBB leakage and lipid peroxidation[60].…”
Section: Discussionmentioning
confidence: 99%
“…Also kaempferol attenuated LPS-induced BBB dysfunction by counteracting the increase of BBB permeability and the degradation of TJs proteins such as occludin-1 and claudin-1, as well as the gap junction protein connexin 43[58]. Regarding metabolites, indole-3-propionic acid was shown to attenuate hypoxic-ischemic-induced BBB leakage in neonatal rats, holding protective effects on rat BMEC cell viability and proliferation, as well as in AJs and TJs proteins modulation[59]. In male Wistar ischemic rats exposed to dusty particulate matter, it was observed that pretreatment with gallic acid reversed BBB leakage and lipid peroxidation[60].…”
Section: Discussionmentioning
confidence: 99%
“…58 Regarding metabolites, indole-3-propionic acid was shown to attenuate hypoxic-ischemic-induced BBB leakage in neonatal rats, holding protective effects on rat BMEC cell viability and proliferation, as well as in AJs and TJs proteins modulation. 59 In male Wistar ischemic rats exposed to dusty particulate matter, it was observed that pretreatment with gallic acid reversed BBB leakage and lipid peroxidation. 60 Indeed, gallic and caffeic acid were shown to protect against hyperglycemia-induced BBB disruption in bEnd.3 cells, with caffeic acid increasing claudin-5, occludin, ZO-1 and ZO-2.…”
Section: Discussionmentioning
confidence: 99%
“…17 Additionally, due to its anti-inflammatory properties, IPA also demonstrates potential therapeutic benefits for neurodegenerative diseases characterized by chronic inflammation. 18 Furthermore, it holds promise for alleviating AD. Abundant research suggests that tryptophan can be metabolized by gut microorganisms like C. sporogenes into IPA.…”
Section: Introductionmentioning
confidence: 99%